ENHANCED ONLINE LIBRARY MANAGEMENT SYSTEM: ITS IMPACT ON STUDENTS’ LEARNING EXPERIENCE AND ACADEMIC PERFORMANCE IN INQUIRIES, INVESTIGATION, AND IMMERSION - Aloc, Viela Rose R.; Bustamante, Rose-Anne V.; Calong, Carl Lorenz I.; Remoroza, Juneto Marco P.; Talaman, Eduardo M. (Galaxy International Interdisciplinary Research Journal, 2023)
The purpose of this study is to determine how the enhanced online library management system impacts the learning experience and academic performance of grade 12 students’ in inquiries, investigation, and immersion. True-experimental design was implemented. Collection of inquiries, investigation, and immersion average and likert-scale questionnaire was administered to grade 12 students. The data were analyzed using both descriptive and inferential statistics. The study revealed that the enhanced online library management system positively impacted the respondents' learning experience and academic performance. Thus, it revealed that strand is insignificant in the learning experience of students, though, it is significant in their academic performance. The study concluded that the learning experience and academic performance of the respondents who used the enhanced online library management system is significantly different than those who did not use the aforementioned website. This study examines the impact of the enhanced online library management system on academic performance and learning experience in inquiries, investigation, and immersion. The study concentrated solely on grade 12 senior high school students, limited to 40 respondents. The findings offer practical value in widening the accessibility of students in learning materials. This study concludes the impact of the enhanced online library management system improved the learning experience and academic performance of students that will benefit and assist a school library and teachers in providing information accessibility through the enhanced and new features offered by a website such as Quick Response features, Video Lessons Page, Book Page, and Announcement page.